Protected Cultivation and Drip Fertigation Technology for Sustainable Food Production - Hasan, M. (International Journal of Economic Plants, 2016)
Protected cultivation is one of the most promising areas of agriculture in the current context. It is an upcoming and alternative production system involving high-tech and intensive practices mainly for urban and export demands of horticultural and ornamental crops for food, nutrition and economic security. Burgeoning population, fragmentation of land holdings, depletion and erosion of natural resources are all adversely affecting agricultural productivity. The main purpose of protected cultivation is to create a favourable environment for the sustained growth of the crop so as to realize its maximum potential even under adverse climatic conditions. Protected cultivation technology, using different structures offers several advantages to produce vegetables, flowers, hybrid seeds and plants of high quality with minimum risks due to uncertainty of weather and also ensuring efficient use of land, water and other resources. Area under protected cultivation in India is about 50,000 hectares only. Maharashtra is leading state in India, followed by Karnataka and Himachal Pradesh. Apart from protected cultivation Drip irrigation, is also the best available technology for the efficient use of water for growing horticultural crops in large scale on sustainable basis. Irrigation water savings ranging from 36-79% can be affected by adopting a suitable drip irrigation system. At present, there is a large gap between the demand and production of these crops to meet both quantitative and qualitative needs of domestic and export markers which are difficult to be bridged with the traditional cultivation practices. Thus protected cultivation and precision farming of horticultural crops has great potential to enhance the income especially of small farmers if appropriate technology interventions are made.